The sncRNA Zoo: a repository for circulating small noncoding RNAs in animals. Issue 9 (2nd April 2019) - Fehlmann, Tobias; Backes, Christina; Pirritano, Marcello; Laufer, Thomas; Galata, Valentina; Kern, Fabian; Kahraman, Mustafa; Gasparoni, Gilles; Ludwig, Nicole; Lenhof, Hans-Peter; Gregersen, Henrike A; Francke, Richard; et al.
Abstract: The repertoire of small noncoding RNAs (sncRNAs), particularly miRNAs, in animals is considered to be evolutionarily conserved. Studies on sncRNAs are often largely based on homology-based information, relying on genomic sequence similarity and excluding actual expression data. To obtain information on sncRNA expression (including miRNAs, snoRNAs, YRNAs and tRNAs), we performed low-input-volume next-generation sequencing of 500 pg of RNA from 21 animals at two German zoological gardens. Notably, none of the species under investigation were previously annotated in any miRNA reference database. Sequencing was performed on blood cells as they are amongst the most accessible, stable and abundant sources of the different sncRNA classes. We evaluated and compared the composition and nature of sncRNAs across the different species by computational approaches. While the distribution of sncRNAs in the different RNA classes varied significantly, general evolutionary patterns were maintained. In particular, miRNA sequences and expression were found to be even more conserved than previously assumed. To make the results available for other researchers, all data, including expression profiles at the species and family levels, and different tools for viewing, filtering and searching the data are freely available in the online resource ASRA (Animal sncRNA Atlas) athttps://www.ccb.uni-saarland.de/asra/ .